Representations of strongly algebraically closed algebras - Molkhasi, A.; Shum, K.P. (Algebra and Discrete Mathematics, 2019)
We introduce the notion of q′-compactness for MV-algebras. One of the main results of the paper is a characterization of a class of orthomodular lattices that are horizontal sums of strongly algebraically closed algebras.